The Effect Of Work Discipline And Work Supervision On Work Productivity Of BPJS Ketenagakerjaan Employees In North Medan Branch - Sandriani, Putri; Harahap, Kartini (Jurnal Sosial Sains dan Komunikasi, 2023)
The purpose of this study was to determine the effect of work discipline and work supervision on the work productivity of employees at BPJS Ketenagakerjaan, North Medan Branch. Then the next goal is to find out the effect of work discipline and work supervision together on the work productivity of employees at BPJS Ketenagakerjaan North Medan Branch. The form of research used is a quantitative method with an associative approach involving 42 employees as the research sample. The sampling technique is saturated sampling. The data collection used is a questionnaire using a Likert scale. The data analysis technique used instrument test of reliability validity, classical assumption test and hypothesis test using multiple linear regression analysis using SPSS.The results of the research conducted indicated that work discipline and work supervision have a significant effect either partially or jointly on the work productivity of employees at BPJS Ketenagakerjaan, North Medan Branch by 79.0%. This means that the behavior of work discipline and work supervision that is owned by employees is sufficient to explain their work productivity, the higher the behavior of work discipline and the better work supervision, it will increase work productivity.